How do you simplify (4x+8) /( 3x)* (9x^2) / (x+2)?

1 Answer
Aug 2, 2015

E = 12x

Explanation:

Your starting expression is

E = (4x+8)/(3x) * (9x^2)/(x+2)

You can simplify this expression by factoring the numerator of the first fraction and cancelling like terms that can be found on the numerator and denominator of the resulting fraction.

The numerator of the first fraction can be rewritten as

4x+8 = 3 * (x+2)

Likewise, you can write the numerator of the second fraction as

9x^2 = (3x)^2 = 3x * 3x

This means that you have

E = (4 * color(red)(cancel(color(black)((x+2)))))/(color(blue)(cancel(color(black)(3x)))) * (color(blue)(cancel(color(black)(3x))) * 3x)/color(red)(cancel(color(black)((x+2)))) = 4 * 3x = color(green)(12x)